Zawód – żona polityka. Rola kobiet w kreowaniu wizerunku politycznego - Przystacka, Dagmara (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The most recent presidential election at the time of writing, the term of Aleksander Kwaoeniewski, everyday political life and the recent presidential campaign have demonstrated how important the role of a politician’s wife has become. That a wife may act as the president of a foundation, as an advisor, as a chair of an association, as an activist defending the rights of children and any related activity, is one of the elements of the image of the husband – a politician. When asked whether their decision to get married would have been different if they had known many years ago that their husband would become involved in politics, the answer is „No”.Women are satisfied living with a politician, although they generally admit that this requires sacrifice. When something important is happening, everything else has to be neglected. Then they have to be patient, persistent and wise, because only such an attitude can advantageously influence the political images of their husbands.